(untitled) (Research, Society and Development, 2021)
This paper aims to discuss how marketing (which has gained a lot of importance in the digital environment in recent years) can improve the company’s image, when done well and respecting dental ethics, and explaining about the management of dental clinics - since organization of documents, respect for schedules and cost control leads to greater excellence, in addition to reducing expenses and mitigating risks -, thus finding solutions with the purpose of boosting the performance of establishments. This is a literature review, where an electronic search for publications was carried out in the PubMed, Lilacs and Scielo database, using the following keywords, obtained according to the Medical SubjectHeadings (MeSH): dentistry, marketing and management, with the Boolean operator “AND”; 7 papers were selected. It is concluded that it is essential that undergraduate courses in dentistry adopt more effective models on the non-technical subject for the training of new professionals, which will improve the quality of services provided and will enable greater chances of professional and financial success for the company.